Evaluation of Resistant Tea (Camellia sinensis L.) Clones Against Helopeltis bradyi - Dimas Tri Asmara; Rudi Hari Murti; Arman Wijonarko; Enik Nurlaili Afifah (AGRIVITA, Journal of Agricultural Science, 2021)
Helopeltis bradyi is a significant pest that causes yield losses and reduces the quality of tea plantations by piercing and sucking the sap of tea leaves. This pest can be appropriately controlled by using resistant clones. The PGL series (clones) owned by Pagilaran plantation has high yield and quality. However, information their resistance level against H. bradyi is limited. This research was conducted at Pagilaran tea plantation at an altitude of 990 masl. Six PGL clone series (PGL 4, PGL 6, PGL 9, PGL 10, PGL 11, and PGL 15) and control clones (TRI 2025 and Gambung 7) were used as plant materials. Their morphological and biochemical characteristics were determined to evaluate their resistance level against H. bradyi. The results revealed that the score symptoms (under 10%) of PGL 4, PGL 9, PGL 10, PGL 11, and PGL 15 clones were the lowest, so these clones were categorized to be highly resistant. In addition, the total phenol content and trichome density of PGL 4, PGL 10, and PGL 15 clones were the highest. Among them, the PGL 4 clone had the thickest epidermis. These characteristics likely contributed to the morphological and biochemical defence mechanisms of tea plants against H. bradyi.